In commemoration of Dmitriy Vladimirovich Myasoyedov (PH Akademperiodyka, 2023)
On the 24th January 2020, a famous Ukrainian oncologist-surgeon, the Honored Master Of Science and Technology of Ukraine, Doctor of Medical Sciences, Professor Dmitriy Vladimirovich Myasoyedov has passed away on the 89th year of his life. He was born in the city of Pryluky, Chernigov Region of Ukraine in a family cherishing the traditions of intelligence. The impact of his mother, a clinical physician-neurologist, influenced professional choice of Dmitriy Myasoyedov. In 1955, he graduated from Kishinev Medical Institute (Moldavia Republic), wherein Dr. Myasoyedov became one of the best students in theoretical and clinical disciplines. After graduation from the Institute, he was assigned to work as a surgeon in the Regional Hospital of Ryshkany. Through subsequent 5 years of his career as a surgeon and the Head of the Hospital, Dr. Myasoyedov gained wide experience in general surgery and the health organization in the district of his supervision. For the achievements in his practice, Dr. Myasoyedov was awarded The Medal “For Honor in Trade” and the Certificate of Commendation from the local Power. In 1960, Dr. Myasoyedov came to Ukraine where he started his career as an assistant fellow of the Oncology Department in Kyiv Institute for Advanced Training of Physicians (now Shupyk National Medical Academy of Postgraduate Education), where he worked until his death. In 1966, Dr. Myasoyedov has got his first scientific degree of Candidate of Science in Oncology for first domestic introduction of the Valdoni procedure in oncoproctological patients. As an Assistant Professor of the Oncology Department, he pioneered the trend of cryosurgical radical resection for locally-spread gastric and rectal cancers. In cooperation with the construction bureau of Kyiv Institute of Physics, the Academy of Sciences of Ukraine, he designed the devices for cryoapplication named as “KAU-01” and “KAG-03” intended for the radical resection of solid tumors. These purely domestic medical gadgets have permitted the surgeons to apply widely the cryodestruction method as a single modality or in combination with radiation therapy. Dr. Myasoyedov studied and proved the safety and efficacy of a devitalization and the enhanced ablastic impact of intraoperative pre-resection cryodestruction due to immediate peritumoral and intratumoral vasostasis, achieving the reduction of the tumoral mass. He has shown that the tumoral tissue destruction is guaranteed following accurately developed cryodestruction regime. Dr. Myasoyedov demonstrated in clinical practice that the treatment effect depends on the tissue thermophysics properties, the cryoaction cycle, and the close contact between the cooling cap of the cryoinstrument and the tumor surface. Working in experimental and clinical environment, Dr. Myasoyedov has proved the adequacy and safety of the visual and palpation intraoperative estimation and control of the cryodestruction borders in a real time regime, especially for low rectal cancers. These procedures implemented into the clinical practice provided for the essential improvement of five-year survival of the patients. In 1984, Dr. Myasoyedov defended his doctoral thesis entitled “Combined treatment of gastric cancer with the effects of low temperatures”. In 1988, he was awarded the academic title of professor by the speciality “Oncology”. Since 1984, Dr. Myasoyedov became the Head of the Oncology Department. In 1974–1991, Prof. Myasoyedov also held the position of Vice-Rector for Teaching in Kyiv Institute for Advanced Training of Physicians. Within the last years of his life, Prof. Myasoyedov investigated the combined and complex treatment of breast cancer. He has implemented the reconstructive surgery of the mammary gland applying the first Ukrainian mammary gland endoprosthesis “Nubiplant”. In 2000, he performed the first prophylactic mastectomy in Ukraine based on the prognostic data of the genetic analysis. Prof. Myasoyedov supervised four doctoral and five candidate theses devoted to cryodestrucion of lung cancer, hepatic malignances and colon cancer. His scientific direction, cryodestruction in surgical and combined treatment of cancer made him famous within the medical scientific community. The principles of cryodestruction in surgery developed by Prof. Myasoyedov remain significant and largely relevant in today medical practice. Prof. Myasoyedov authored more than 300 scientific papers including 12 textbooks and monographs on various aspects of clinical oncology. His scientific activity was also tightly associated with RE Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, the National Academy of Sciences of Ukraine, where he was the member of the Specialized Council for Thesis Defense on speciality “Oncology”, the member of Editorial Board and Guest Editorial Member of scientific journals “Experimental Oncology” and “Onkologiya”. Dmitriy Vladimirovich Myasoyedov remains in the memory of his family, friends, followers and patients as an outstanding leader, prominent and warm personality, a gifted surgeon, devoted physician and scientist, and gentle intelligent. Editorial Board of “Experimental Oncology”